Preliminary design of ac substation grounding system using improved and evolutionary particle swarm optimisation / Ahmed Nasiru Yahaya - Ahmed Nasiru , Yahaya (2018)
Grounding system design is an important aspect in electrical engineering because it deals with personnel and equipment safety. The electricity supply at homes and industries usually pass through the transmission and distribution substations. The voltage levels at these substations are usually high between 11kV and 500kV or higher. Hence, personnel and equipment operating within the substation domain may be in danger in cases of faults if a proper grounding system is not design for safe dissipation of the overvoltages. Preliminary grounding design is usually performed by proposing a design which meets the grounding requirement without considering cost minimisation. If the cost of the design is considered, trial and error concept is usually used if the requirements are met. However, this method is time consuming and less efficient. Therefore, a new method to minimise the cost of grounding grid design while the requirements are still met is proposed in this work, which is using optimisation methods. In this work, a preliminary grounding system design for an AC distribution substation with a system voltage of 22kV was carried out using improved particle swarm optimisation (IPSO) and evolutionary particle swarm optimisation (EPSO) methods. The number of parallel rows of wires, number of parallel columns of wires, number of grounding rods and length of grounding rods were optimised so that the grid resistance is within the requirement and the cost of the grounding system is minimised. The two methods were compared with other methods used in previous works carried out on different sizes of substation. It was observed that the safety parameters and optimum results obtained from this work yield reasonable results.